Catalogue of representative scales to visualize different coverages in Google Earth - Tristan, A.C. (IOP Publishing Ltd, 2021)
Representative scales were established, based on the zoom level of Google Maps, for generating a catalogue of indicators from the scale-image relationship, into the Google Earth visualization system. It was possible to analyze some functionalities of the visualization system proposed, such as the depth of detail from image resolution and the images return. Therefore, samples of four land use were analyzed. Furthermore, to associate the multilevel mechanism of the visualization in Google Earth, a digital ruler was used as a tool that measures the pixels per inch into the screen. In consequence, it is possible to analyze the changing behaviour from one screen to another. With this, it is feasible to associate a specific mechanism to improve the relationship between the handling of several images covering a limiting territory, and the scales that best represents the themes described. Finally, 893 samples were analyzed in 32 points of the territory, between the coordinates 14 to 33 N and 86 to 119 W. Finally, the error percentage, the variance, and the standard deviation were estimated for determining the variation between the values calculated in different samples. Â© Published under licence by IOP Publishing Ltd.